Influence of Voluntary Contraction Level, Test Stimulus Intensity and Normalization Procedures on the Evaluation of Short-Interval Intracortical Inhibition - Cécilia Neige; Sidney Grosprêtre; Alain Martin; Florent Lebon (Brain Sciences, 2020)
Short-interval intracortical inhibition (SICI) represents an inhibitory phenomenon acting at the cortical level. However, SICI estimation is based on the amplitude of a motor-evoked potential (MEP), which depends on the discharge of spinal motoneurones and the generation of compound muscle action potential (M-wave). In this study, we underpin the importance of taking into account the proportion of spinal motoneurones that are activated or not when investigating the SICI of the right flexor carpi radialis (normalization with maximal M-wave (Mmax) and MEPtest, respectively), in 15 healthy subjects. We probed SICI changes according to various MEPtest amplitudes that were modulated actively (four levels of muscle contraction: rest, 10%, 20% and 30% of maximal voluntary contraction (MVC)) and passively (two intensities of test transcranial magnetic stimulation (TMS): 120 and 130% of motor thresholds). When normalized to MEPtest, SICI remained unchanged by stimulation intensity and only decreased at 30% of MVC when compared with rest. However, when normalized to Mmax, we provided the first evidence of a strong individual relationship between SICI and MEPtest, which was ultimately independent from experimental conditions (muscle states and TMS intensities). Under similar experimental conditions, it is thus possible to predict SICI individually from a specific level of corticospinal excitability in healthy subjects.